2017
DOI: 10.1002/elan.201700272
|View full text |Cite
|
Sign up to set email alerts
|

Isatin Analysis Using Flow Injection Analysis with Amperometric Detection – Comparison of Tetrahedral Amorphous Carbon and Diamond Electrode Performance

Abstract: Isatin is an endogenous indole compound in humans and rodents that has a wide range of biological activity. In rat models, isatin concentrations have been shown to increase in the heart, brain, blood plasma, and urine with stress. Studies on patients suffering from Parkinson's disease have indicated a correlation between progress of the disease and urinary output of the molecule. Isatin is electrochemically active and can therefore be detected with electrochemical techniques. In this work, we compared the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…For example, Qi et al has reported the cathodic lucigenin ECL detection of isatin at a Pt electrode . Swain's group has detected isatin at tetrahedral amorphous carbon electrode by amperometry combined with a flow injection analysis . Rusinek's group reported the electrochemical detection of isatin using a fabricated two 3‐in‐1 boron‐doped diamond (BDD) electrodes .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Qi et al has reported the cathodic lucigenin ECL detection of isatin at a Pt electrode . Swain's group has detected isatin at tetrahedral amorphous carbon electrode by amperometry combined with a flow injection analysis . Rusinek's group reported the electrochemical detection of isatin using a fabricated two 3‐in‐1 boron‐doped diamond (BDD) electrodes .…”
Section: Introductionmentioning
confidence: 99%
“…However, polishing is a tedious and time‐consuming process. Furthermore, glassy carbon is subject to surface fouling and typically undergoes unwanted microstructural changes at the very positive potentials often required to detect target pharmaceuticals and pollutants, like the estrogenic metabolites .…”
Section: Introductionmentioning
confidence: 99%
“…In general, diamond electrodes have emerged as promising alternatives, due to their chemical inertness and high stability . Planar boron‐doped diamond (BDD) thin‐film electrodes have been studied extensively in recent years, and exhibit key properties of resistance to fouling, low background current, and wide working potential window . Structurally, BDD consists entirely of sp 3 hybridized carbon, and is doped with diborane gas (B 2 H 6 ) during thin film growth to increase electrical conductivity .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations